Supplementary Materials: Modeling and Forecasting of Spinach Production in Bangladesh - Das, Keya Rani; Das, Keya Rani; Jahan, Mashrat; Barman, Linnet Riya; Burman, Preetilata (Nepalese Journal of Statistics, 2023)
As mentioned in the manuscript.